Fairness Aspects Of Compensation Arrangements In The Acquisition Of Land For Development For The Public Interest - Gusti Ayu Kade Harry Adhisukmawati, I; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The need for land for development for the public interest is increasingly urgent, while the supply of land is increasingly limited. The fairness and redress mechanisms in the land acquisition are often fraught with problems. This study aims to analyze the fairness aspects of the regulation and the mechanism for providing compensation in the acquisition of land for development for the public interest. This research is normative, and prescriptive, with a regulatory and conceptual approach. The results of the study found that a) the fairness aspect of land acquisition arrangements for the public interest can be seen from the guarantee of adequate compensations stipulated in Law Number 2 of 2012 concerning Land Acquisition for Development for Public Interest, Law Number 11 of 2020 concerning Job Creation, Indonesian Assessment Standard 204, and other laws and regulations that relating to land acquisition. And b) the mechanism for providing compensation is carried out after the assessment is by the Indonesian Assessment Standard 204, Law Number 11 of 2020 concerning Job Creation, deliberations, and validation activities are completed. The payment given can be in the form of money in Rupiah as agreed by the Land Acquisition Committee and the community, then it can be given through a bank account appointed by the Government.